(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Imidazolium salts were produced through different substitutions, including aliphatic chains and phenyl acetamide, resulting in symmetrically substituted salts. The Silver(I)-NHC complex was synthesized by reacting symmetrically substituted imidazolium salts with Ag2O, employing an in-situ the depr0tonation technique to obtain the desired structures with high yield. The Silver(I)-NHC complex was then utilized as a transfer reagent through the transmetallation technique to generate respective palladium (II)-NHC complexes. The platinum (II)-NHC complex synthesis was set under an atmosphere of nitrogen, using anhydrous toluene. The recently developed compounds were assessed for efficacy against three human cancer cell lines —gastric adenocarcinoma (AGS), and colon carcinoma (HT29), with the normal cell line (MCF-12A) serving as a control, using the MTT method. The characterization of the complexes involved various spectroscopic techniques, including 1HNMR, 13CNMR, Mass, UV-Vis, FT-IR, and determination of melting point.